Evaluation of the Welfare of Piece Workers at Oil Palm Plantations in West Kutai, East Kalimantan - Murlianti, Sri; Nanang, Martinus; Sukapti; Rahman, Adi; Purwaningsih (Research and Social Study Institute, 2022)
The oil palm industry was expected to become a substitute for the main source of foreign exchange for East Kalimantan, which to date is still dependent on coal mining. Since 2018, the Governor of East Kalimantan has launched the Green Kaltim program to accelerate the realization of oil palm as a new mainstay of East Kalimantan’s economy. PT Laskar (a pseudonym) in West Kutai Regency is one of the largest oil palm companies in East Kalimantan and has started to operate in the 1980s. This article is the result of an initial investigation concerning the welfare of piece workers at oil plam plantations to collect data that will be used to prepare labor rights advocacy activities as a form of community service. The investigation was carried out using the participant observation methods. The team visited workers' barracks, socialized with them, strengthened discussions, and together formulated the scope of the problems they faced. The evaluation results reveal that the piece workers are put in a very vulnerable position, both in terms of job certainty, income, health, and assistance from outside parties when experiencing problems. Weak control from the state perpetuates these inhumane labor practices, allowing workers to live in limitations and minimal supports, both from the company and the local government.